Influence of evaporation drying on the porous properties of carbon/carbon composite xerogels - Kraiwattanawong, Kriangsak; Sano, Noriaki; Tamon, Hajime (My University, 2021)
Carbon/carbon (C/C) composite xerogels dried by evaporation were prepared in this study to observe the change of their porous properties and their morphology by nitrogen sorption apparatus and a scanning electron microscope. Resorcinol and formaldehyde (RF) sols as a matrix phase and cotton fibers (CF) as a dispersed phase were mixed and gelated to be CF/RF composite hydrogels. The composite hydrogels were exchanged by t-butanol (TBA), dried by evaporation at 50◦C, and carbonized at 1000◦C to become the C/C composite xerogels. The results show that the CF addition does not decrease the mesoporous properties of the C/C composite xerogels. Moreover, the CF addition can alleviate the pore shrinkage, and it can maintain the mesopore structure. The mesopore size and the micropore size of C/C composites are insignificantly changed because the CF addition and the solvent exchange using TBA may suppress the pore shrinkage despite the gas-liquid interface existing during the evaporation drying.
Keywords: Carbon xerogel; Composite; Evaporation drying; Nitrogen adsorption; Porous properties